A Study of Siberia's Medicinal Plants Used in Homeopathy - Nekratova, Anna Nicolaevna; Kosmodemyanskiy, Leonid Vladimirovich (Homeopathy, 2019)
Background A current priority of national health care in Russia is to expand the range of drug substances, based on naturally occurring compounds, to use for treating socially significant diseases, such as cancer and cardiovascular diseases.Objective The main objective of our study was to compile a contemporary list of Siberia's ‘homeopathic plants’, describing for each plant the corresponding therapeutic indications or main symptoms of disease.Methods The textbook, Global Resources of Homeopathic Medicinal Raw Materials, was used to scrutinize the 709 species that are allowed for use in Russia, designating each of the 709 as either indigenous or non-indigenous to the region of Siberia. A homeopathic repertory, containing description of more than 1,800 single-component homeopathic medicines, was used to identify Siberia's medicinal plants used in homeopathy, along with the medical indications of each.Results The medicinal plants of Siberia used in homeopathy comprise 137 species of flowering plants, gymnosperms and sporophytes, belonging to 52 families. The most represented are the Compositae, Rosaceae, and Lamiaceae families.Conclusion The inventory of Siberian plants has allowed us to identify the plants of this region used in homeopathy and will help to inform research on additional species with the potential for introduction into homeopathic practice.
Keywords: homeopathy; medicinal plants; Siberia